Length-weight relationship and condition factor of tonguesole Cynoglossus cynoglossus Hamilton 1822 (Pisces: Cynoglossidae) in Pabean Bay Indramayu, West Java - Arinie Gustiarisanie; M. F. Rahardjo; Yunizar Ernawati (Jurnal Iktiologi Indonesia, 2016)
Length - weight relationship and condition factor are two important parameters in fisheries biology. Both of these parameters are equally used for estimating the fish stocks. This study aimed to determine the length - weight relationship and to evaluate the condition factor of tonguesole in Pabean Bay. Fish collection was carried out monthly from January to December. A total of 613 fish consists of 290 males and 323 females. Total length of males and females fish ranged from 46 to 117 mm and 61 to 126 mm with body weight ranged from 0.57 to 9.49 g, 2.36 to 16.72 g, respectively. The length - weight relationship was W = 2x10 - 5 L 2.73 (males and females), W = 5x10 - 5 L 2.56 (males), W = 2x10 - 4 L 2.22 (females) and the condition factor ranged from 0.83 to 1.22 (males), 1.29 to 1.70 (females). These results indicate that the growth pattern of fish was negative allometric and the condition of females fish was better than males. Abstrak Hubungan panjang - bobot dan faktor kondisi merupakan dua parameter penting dalam biologi perikanan. Kedua para - meter ini sama - sama digunakan dalam pendugaan stok ikan. Penelitian ini bertujuan untuk menentukan hubungan panjang - bobot dan mengevaluasi faktor kondisi ikan lidah di Teluk Pabean. Pengambilan ikan contoh dilakukan dalam interval waktu satu kali dalam seb ulan sejak bulan Januari sampai Desember 2015 , menggunakan alat tangkap jaring dan sero. Ikan contoh yang tertangkap sebanyak 613 ekor , terdiri atas 290 ekor ikan jantan dan 323 ekor ikan betina. Panjang total ikan jantan dan betina berkisar 46 - 117 mm dan 61 - 126 mm dengan bobot tubuh ikan jantan dan betina berkisar 0,57 - 9,49 g dan 2,36 - 16,72 g . Hubungan pa njang - bobot ikan lidah adalah W = 2x10 - 5 L 2,73 (jantan dan betina), W = 5x10 - 5 L 2, 56 (jantan), W = 2x10 - 4 L 2, 22 (betina) dan faktor kondisi ikan berkisar 0,83 - 1,22 (jantan) , 1,29 – 1,70 (betina). Hasil ini menunjukkan bahwa pola pertumbuhan ikan bersifat alometrik negatif dan kondisi ikan betina lebih baik daripada ikan jantan.